Jorge el Curioso en el hospital - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977. (New York : Scholastic, 1993)
A curious monkey goes to the hospital after swallowing a piece of jigsaw puzzle.
Translation of: Curious George goes to the hospital.
Accelerated Reader AR
Keywords: Monkeys -- Fiction; Medical fiction; Spanish language materials; Fiction